Kinetics of the polarization reversal process in a non-constant applied electric field and the generalized superposition principle - Leal Ferreira, G. F.; Moreno, R. A. [UNESP] (Taylor & Francis, 1996)
We analyze the results on polarization reversal by H. von Seggern and T. T. Wang (J. Appl. Phys., 56, 2448 (1984)) under the assumption of validity of a superposition principle in terms of a conveniently defined intrinsic time, as has been done tentatively in other fields. The delayed responses of the ferroelectric to the change of the maximum attainable polarization induced by the changing electric field are linearly summed up using two largely different relaxation functions. It is found that despite the large time scale span used in those experiments, the fitting is insensitive to the chosen relaxation function. The good fitting achieved over the whole time scale, in both cases, indicates the soundness of the defined intrinsic time concept which leads to the linear superposition principle.
Keywords: Generalized superposition principle; Polarization reversal kinetics; Dielectric relaxation; Electric field effects; Ferroelectric materials; Intrinsic time concept; Relaxation functions; Polarization